MEDIA INTERTEXT IN SOCIO-CULTURAL IMPACT’S REALIZATION - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2023)
High-quality provision of information: both to key figures and at the social level, is the most important factor in both success in the present and management of the future. Accordingly, an essential issue of public security is the state and dynamics of the information sphere [1-7]. So the realization of a holistic information policy does not contradict, but, on the contrary, relies on the competition of approaches, opinions and information resources. But this is not enough. In particular, the information plane of sovereignty, the development of information infrastructure, the availability of modern information and telecommunication-cybernetic means, is raising the level of media culture. Moreover, the emphasis on hybrid wars and special operations tends to turn the information sphere, the public climate and social well-being into key issues of global, regional and national security. For example, propaganda and agitation allows you to influence the perception, and sometimes even form the reference points for the crystallization of the worldview. The high efficiency of information weapons in processing a specific person and the population as a whole highlights the information sphere as an important component of hybrid pressure. And the digitalization of life opens up depths of alienation and exploitation based on manipulation and inequality.